Process evaluation of an integrated community-based intervention for promoting health equity in children in a new residential development area - Stephan Voss; Julia Bauer; Caroline Jung-Sievers; Graham Moore; Eva Rehfuess; Valerie Zu Rhein; Michaela Coenen (BMC, 2024)
Abstract Background Reducing health inequities for children from a disadvantaged background is an important task in public health. While intersectoral partnerships are a promising way to achieve this, few studies have examined the factors influencing the success of these interventions. In this study, we conducted a process evaluation of the integrated community-based intervention Präventionskette Freiham that the city of Munich, Germany, has implemented in a new residential development area. The aim was to investigate the implementation process as well as barriers and facilitators. Methods Following a mixed methods approach, we collected data from different core groups making up Präventionskette Freiham from April 2020 to August 2022, exploring their perspective on the implementation process. We conducted repeated qualitative interviews with the network coordinators and eleven local professionals from institutions engaged with or relevant for the intervention. We also undertook a focus group with four members of the advisory group representing the three municipal departments guiding the intervention. Ego-centered network maps were drawn by the network coordinators to chart the development of the network. Subsequently, we also conducted an online survey with local network members. Results At the early stage of the implementation process, the intervention was able to integrate actors from different sectors, serving as a platform for mutual exchange. However, the network produced limited output. According to the interviews, this may be mainly attributable to the early development status of the area. We identified seven topics that may act as facilitators or barriers to implementation of Präventionskette Freiham: (1) availability of resources, (2) political and administrative support, (3) the network coordinators, (4) network-internal processes, (5) trans-institutional cooperation, (6) perceived benefits of engagement, and (7) the output of the network. Conclusions The early development status of the area was a challenge for the intervention. This emphasizes the need to carefully consider context when planning and implementing integrated community-based public health interventions in new residential development areas.